THE PROCESS OF CONTINUOUS DEVELOPMENT (IMPROVEMENT) AND ITS EFFECTS ON ORGANIZATIONAL PERFORMANCE IN THE DEPARTMENT OF LANDS AND SURVEY - Mutti- Assaf, Abdel; Sawalhah, Ayyoub; Al-Tarawneh, Hussien (European Scientific Journal, ESJ, 2013)
The research paper aims to build a comprehensive model of the organization and to the continuous development and improvement process, so as to be a methodological basis the helps researchers in possessing a comprehensive that will enable them to conduct the researches in the field of continuous development. It also aims to measure the effect of continuous development processes on the organizational performance in department of lands and survey and measuring the levels of continuous development in the department. 220 questionnaire form papers were distributed randomly on the study population, and 203 of them were answered and delivered back. Statistical analysis was conducted on them. The research employed field study with random sampling, and descriptive and analytical methods of research. The results firmly showed the public weakness in all constituents of the continuous development process , and that the effect of the continuous development process on the organizational performance which is represented in five total circles : the organization philosophy , its general system , its administrational processes , its operational processes , and processes organization maintenance itself was more weak , and that even the effect in the whole development process itself was also weak . These results impose the higher management conducting comprehensive assessments and preparing development plan that should include all the organizational capability constituents so as to be complied with total quality management TQM criteria.